2008
DOI: 10.1179/147683008x301450
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive findings of an exploratory trial of docosahexaenoic acid and lutein supplementation in older women

Abstract: These exploratory findings suggest that DHA and lutein supplementation may have cognitive benefit for older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
198
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(212 citation statements)
references
References 36 publications
7
198
2
2
Order By: Relevance
“…Furthermore, the concentration of Z in blood serum is inversely associated with the severity of white matter lesions in the brains of nondemented older adults (den Heijer et al, 2001). In a postmortem series, higher concentrations of L and Z in the brain were associated with better cognitive function at the time of death (Johnson et al, 2011). It has also been shown that the concentration of carotenoids comprising MP in the retina is highly correlated with carotenoid levels in the cerebellum and occipital cortex of macaque monkeys (Vishwanathan et al, 2013).…”
mentioning
confidence: 81%
“…Furthermore, the concentration of Z in blood serum is inversely associated with the severity of white matter lesions in the brains of nondemented older adults (den Heijer et al, 2001). In a postmortem series, higher concentrations of L and Z in the brain were associated with better cognitive function at the time of death (Johnson et al, 2011). It has also been shown that the concentration of carotenoids comprising MP in the retina is highly correlated with carotenoid levels in the cerebellum and occipital cortex of macaque monkeys (Vishwanathan et al, 2013).…”
mentioning
confidence: 81%
“…Johnson et al performed a small clinical trial in 60-80 year-old women that were randomized to receive DHA (800 mg/day), lutein (12 mg/day), or a combination of DHA and lutein. Each treatment alone or in combination improved performance in a Verbal fluency test and only the combination of lutein and DHA improved performance in other tests such as Word list, Shopping list and MIR apartment tests sugesting a potential synergistic effect of both nutrients (Johnson et al, 2008).…”
Section: Lutein and Zeaxanthin: The Function In The Brainmentioning
confidence: 99%
“…A reliable and commonly used proxy for macular pigment levels and hence lutein and zeaxanthin levels is macular pigment optical density (MPOD). MPOD correlates with processing speed and cognitive performance in healthy elderly subjects as well as those with mild cognitive impairment [25][26][27].…”
Section: Neural Processingmentioning
confidence: 99%